STRATEGI PERSONAL SELLING DALAM DIFUSI INOVASI PEMASARAN DI PT. MASTERSYSTEM INFOTAMA JAKARTA - Innocentia Magda; Husnita Husnita (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
Technological innovation is a highly anticipated aspect for business actors in this digital era. Advances in automation and artificial intelligence offer significant opportunities for industries to reduce operational costs, especially in handling repetitive or clerical tasks that can be replaced by machines or robots. The application of advanced technology not only improves efficiency but also accelerates business processes and enhances service quality. PT. Mastersystem Infotama, which has become one of the leading providers of Information and Communication Technology infrastructure in Indonesia, plays a crucial role in helping companies adopt technological innovations. As a reliable business partner, PT. Mastersystem Infotama not only builds and integrates technology systems but also provides consultants who offer high-quality solutions. Since its establishment in 1994, PT. Mastersystem Infotama has served over 1000 clients in Indonesia. Supported by renowned principals such as Cisco Systems, Hewlett Packard Enterprise, F5, Cloudera, Google, and NetApp, the company offers various solutions including data center and cloud infrastructure, enterprise collaboration, big data & analytics, digital business management, adaptive security architecture, and more. This study examines the role of personal selling in the diffusion of marketing innovation at PT. Mastersystem Infotama. Using personal selling approaches, the company effectively communicates the benefits of technological solutions to potential clients. This research focuses on the impact of personal selling on innovation adoption, highlighting the stages of knowledge, persuasion, decision, implementation, and confirmation in the innovation diffusion process. The findings indicate that a well-executed personal selling strategy, combined with collaborative efforts among marketing communication, account management, and solution architects, significantly enhances client relationships and drives the successful adoption of technological innovations. Keywords: Diffusion of Innovation, personal Selling, Technology Marketing, communication strategy.